2021
DOI: 10.33024/jkm.v7i2.4140
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Riwayat Penyakit Infeksi Dengan Kejadian Stunting Pada Anak Usia 12-59 Bulan

Abstract: HISTORICAL RELATIONSHIP OF INFECTIOUS DISEASE WITH STUNTING EVENTS IN CHILDREN AGED 12-59 MONTHS  Background:Stunting events in the highest Central Lampung district are in Pubian Sub-District, Kecamanatan Anak Tuha, Seputih Agung Sub-District, and Seputih Raman Sub-District, In Seputih Raman sub-district there are 2 Working Areas of Puskesmas Seputih Raman with 4 villages stunting data obtained as many as 153 children, and Rama Indra Health Center with 5 villages with the number of stunting children as many as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 3 publications
2
5
0
11
Order By: Relevance
“…In line with research conducted by Trio Subarto, Linawati Novikasari, Setiawati (2021), Seputin Raman Health Center, Central Lampung, this study showed that there were 45 toddlers (22.1%) suffering from infectious diseases with stunting conditions, and 57 toddlers (27.9%) with stunting conditions. Stunting has never suffered from an infectious disease.…”
Section: Resultssupporting
confidence: 87%
“…In line with research conducted by Trio Subarto, Linawati Novikasari, Setiawati (2021), Seputin Raman Health Center, Central Lampung, this study showed that there were 45 toddlers (22.1%) suffering from infectious diseases with stunting conditions, and 57 toddlers (27.9%) with stunting conditions. Stunting has never suffered from an infectious disease.…”
Section: Resultssupporting
confidence: 87%
“…Thus, it is necessary for each individual to improve their knowledge about the importance of personal hygiene. Besides, maintaining environmental and food hygiene can prevent the emergence of various diseases, especially in children (19).…”
Section: Discussionmentioning
confidence: 99%
“…Didapatkan nilai OR sebesar 1,072 artinya bahwa anak yang pernah menderita suatu penyakit akan berpeluang atau beresiko 1 kali mengalami stunting. Hasil penelitian ini didukung oleh penelitian terdahulu yang menyatakan bahwa riwayat penyakit, khususnya penyakit infeksi berhubungan dengan kejadian stunting pada anak usia 12-59 bulan (Subroto, et al, 2021).…”
Section: Pendahuluanunclassified